A Cross-Sectional of Syrians’ Knowledge of Diabetes Mellitus and Hypertension Management - Swed, Sarya; Alibrahim, Hidar; Bohsas, Haidara; Amir Rais, Mohammed; Shoib, Sheikh; Sawaf, Bisher; Abdelazeem, Basel (International Journal of Medical Students, 2023)
Background: Diabetes and hypertension are the two most common types of non-communicable diseases (NCDs) impacting people globally. There is no prior research on the Syrian population’s knowledge and treatment of hypertension and diabetes, so it is crucial to assess how the Syrian population acknowledges and perceives these illnesses. This research intends to assess the level of hypertension and diabetes-related awareness, knowledge, attitude, and practices among Syrian individuals. Methods: A cross-sectional study was conducted between 1 August and 25 August 2022 to assess adult awareness, knowledge, attitude, and behavior about hypertension and diabetes. The questionnaire for the study was developed based on previous research, and the inclusion criteria for the sample were Syrian residents older than 18 who presently live in Syria. On the questionnaire, there were four sections: sociodemographics information, WHO STEPS survey instrument on knowledge of and lifestyle determinants for hypertension and diabetes, respondents’ knowledge of and comprehension of hypertension and diabetes, and respondents’ awareness of these disorders. Results: Among 976 participants, (65.8%) were females. Participants reported hypertension caused by (90.1%) stress, (78.2%) old age, (69%) anxiety, and (38.6%) drug usage. High salt consumption (87%), genetics (82.1%), and obesity (78%) are all risk factors for hypertension. In addition, minimizing salt consumption (92.4%), regular exercise (87.2%), and avoiding anxiety (85%) are preventative measures for hypertension. Participant answers to hypertension consequences were (75.8%) foot ulcer and (74%) eyesight loss. Primary and middle school educational status participants had greater hypertension knowledge (92.3%) than other educational levels. Alcohol use was linked to hypertension knowledge (P < 0.05). Participants whose lifestyles did not include alcohol use had a higher hypertension knowledge level (90.3%). Participants with a family history of diabetes have a greater knowledge of hypertension (92%) than those without (66.9%). Almost age groups have shown good knowledge of diabetes, especially participants aged above 55 (93.8%). However, most individuals have examined blood pressure (82.3%), whereas fewer than half had screened for blood sugar (64.4%). 82.2% of individuals check their blood pressure frequently, whereas 6.2% monitor their blood sugar. Men have a higher hypertension knowledge than females (mean=8.39, SD=2.02), P-value< 0.05, and knowledge of hypertension among participants was shown to be higher among those in good income status than other economic levels (mean=8.34, SD=1.98), P-value< 0.05. Participants between the ages of 40 and 55 showed better knowledge of diabetes compared to other age groups (mean=11.32, SD=2.54), P-value< 0.05; as well, men demonstrated greater knowledge of diabetes than females (mean=10.76, SD=2.79), P-value< 0.05. Conclusion: Our results demonstrated that the Syrian population has a good to moderate understanding of hypertension and diabetes. However, there is still a shortage of standardized, regular screening practices. Since individuals remain involved in unhealthy lifestyle habits, it is vital to provide accurate information about hypertension and diabetes.